The function and manipulation of demonstrative reference in French-English translation - Moindjie, Mohamed Abdou (Penerbit Universiti Kebangsaan Malaysia, 2023)
Demonstrative reference, a form of verbal pointing, is one of the subcategories of cohesive reference. This paper aims to describe demonstrative reference in French-English translation and to explore underlying shift factors. For this purpose, this paper investigates differences and similarities, describes function and manipulation, and determines factors that bring about translation shifts of demonstrative reference. The investigated texts are literary texts whose findings are expected to reflect other genres. The research is a product-oriented descriptive study on demonstrative reference; it follows Halliday and Hasan’s theory (1976) of cohesion, Catford’s theory (1965) of translation shifts, and Vinay and Darbelnet’s theory (1995) of translation procedures. Mixed methods are opted for convenience to conduct the research. The texts under study are read; then, the data are identified, collected, categorised and analysed manually. The investigation reveals that some language peculiarities and preferences necessitate some cohesive shifts, which enhance the cohesion of demonstrative reference in both ST and TT. The research, therefore, indicates that language peculiarities and preferences determine the mechanism of some shifts and the translation procedures of demonstrative reference from French to English.